ADMINISTRATIVE REFORMS OF THE EUROPEAN SOCIAL PROTECTION SYSTEMS: TRENDS AND CHALLENGES (Annual of the Faculty of Philosophy in Skopje, 2019)
Initiatives for social reforms are part of the governmental agendas of almostall European countries. The introduction of support for the households by guaranteeingminimum incomes, activation of the social assistance beneficiaries, as well asdelivery of integrated services in the local community are the main challenges of thecontemporary social protection systems.Reflecting the significance of institutions (establishment, organization andadministrative capacity) as a key condition for achievement of socially-accepted goals,European countries, in the last few decades, have been implementing administrativereforms of social protection systems. The countries are searching for improved institutionalarrangements for maximization of policy effects directed towards social inclusionand reduction of social tensions in the societies. In most cases, countries introduceadministrative modalities based on managerial doctrines of governing (newpublic management), while others experiment with a certain form of decentralizationwhich usually includes initiatives for local provision of social services and, in certaincases, integration with employment services. Yet, although a part of the administrativereforms are being implemented with the same purpose, they lead to differentinstitutional solutions as a result of the social context in which they are framed.This article gives an overview of the trends in the development of the socialprotection systems of the European countries, which despite the efforts for convergenceof social policies and the creation of a unified social model, continue to showdiversity of legal and institutional solutions at the national level.
Keywords: SOCIAL PROTECTION; SOCIAL SERVICES; INSTITUTIONAL FRAMEWORK; ADMINISTRATIVE REFORMS